Effects of additive sensory noise on cognition - Sherman, Sage O.; Greenstein, Maya; Basner, Mathias; Clark, Torin K.; Anderson, Allison P. (Frontiers in Human Neuroscience, 2023)
Background: Adding noise to a system to improve a weak signal’s throughput is known as stochastic resonance (SR). SR has been shown to improve sensory perception. Some limited research shows noise can also improve higher order processing, such as working memory, but it is unknown whether SR can broadly improve cognition. Objective: We investigated cognitive performance while applying auditory white noise (AWN) and/or noisy galvanic vestibular stimulation (nGVS). Methods: We measured cognitive performance (n=13 subjects) while completing seven tasks in the Cognition Test Battery (CTB). Cognition was assessed with and without the influence of AWN, nGVS, and both simultaneously. Performance in speed, accuracy, and efficiency was observed. A subjective questionnaire regarding preference for working in noisy environments was collected. Results: We did not find broad cognitive performance improvement under the influence of noise (p> 0.1). However, a significant interaction was found between subject and noise condition for accuracy (p = 0.023), indicating that some subjects exhibited cognitive changes with the addition of noise. Across all metrics, noisy environment preference may trend to be a potential indicator of whether subjects will exhibit SR cognitive benefits with a significant predictor in efficiency (p=0.048). Conclusions: This study investigated using additive sensory noise to induce SR in overall cognition. Our results suggest that using noise to improve cognition is not applicable for a broad population; however, the effect of noise differs across individuals. Further, subjective questionnaires may be a means to identify which individuals are sensitive to SR cognitive benefits, but further investigation is needed.